Effect of Plant Density and Planting Dates on Pigeonpea Blister Beetles (Mylabris pustulata Thunberg; Coleoptera: Meloidae) Population in Southeastern, Nigeria - S. A. Dialoke; E.C. Enujeke; S.U. Awere; C.O. Echerobia; H.I. Aigbe; N.O. Azubuike; K.J. Nnadi (Current Research Progress in Agricultural Sciences Vol. 9, 2025)
There are limited documents recorded on the population of Mylabris pustulata at varying plant densities of improved pigeonpea in the rainforest agro-ecological region of Southeastern Nigeria. There is limited documentation on the optimal planting time during which the population of M. pustulata is minimal. The early maturing pigeonpea cultivar (ICPL 84023) was evaluated to ascertain the extent of protection to which plant densities and dates of planting will have on the population of blister beetles (Mylabris pustulata Thunberg (Coleoptera: Meloidae). A field trial was carried out at the Postgraduate Teaching and Research Farm, Department of Crop Science and Technology, Federal University of Technology, Owerri Imo State in April, July and October 2009 and repeated in 2010. The experiment was laid out in a 3 x 4 factorial and treatments consisted of four plant populations namely: 190,474 plants ha-1, 125,000 plants ha-1, and 80,000 plants ha-1, 55,556 plants ha-1 with three planting dates, April, July, and October. All data collected were subjected to analysis of variance using Genstat Discovery Edition 3 (2009). The result showed a high population of M. pustulata at higher plant densities than at lower plant densities. Also, the April planting season recorded a very high population of M. pustulata on the pigeonpea while there was an absence of the blister beetles during the July and October planting seasons. The absence of M. pustulata on pigeonpea flowers during the July and October planting seasons indicated that sowing time is an important factor influencing the population of M. pustulata. Appropriate plant density and time of sowing may be an important integrated management of the M. pustulata population in this locality. Based on the findings, low-density planting in July is recommended to reduce the pest population and optimize the yield of pigeonpea.